Rozkład Wirowości w Oscylującej Warstwie Przyściennej Wokół Cylindrycznego Ciała - Paczyńska, H. (Engineering Transactions, 1967)
The vorticity in the wake behind of an oscillating body depends on the vorticity distribution on the body and near it. The generation of vorticity in an incompressible fluid is due to the viscosity which acts above all in the boundary layer. The object of this paper is to analyse the vorticity distribution in the boundary layer around a cylindrical body. The problem of velocity distribution in such a layer was considered by Lighthill in [2]. His results are used in this paper as a starting point. The calculations are made for the two limiting cases, when ω  V/l > 1 and ω V/l < 1; V is the velocity of potential flow, undisturbed by the presence of the body, l - the characteristic length of the body, and ω - the frequency of oscillation. The dependence of the vorticity distribution on the shape of the body is investigated.